(untitled) (Experimental biology, 2015)
We studied the effect of entering in the soil before sowing the seeds of winter wheat varietie “Bogarnaya-56” of mycorrhizal fungi inoculum and pasty suspension of blue green and green algae. Almost half of the tested species of microalgae induced stimulation of growth processes wheat, increasing plant height of 6-12%, ear length at 15-39%. The greatest effect on the structure of the wheat crop had the blue-green algae. The number of grains per spike and 1000-grain weight were increased under the influence of Anabaena sp., A.laxa, A.Arnoldii, Amorphonostoc paludosum.